Can a modified thrombolysis in myocardial infarction risk score outperform the original for risk stratifying emergency department patients with chest pain?. Issue 2 (22nd January 2009) - Body, R; Carley, S; McDowell, G; Ferguson, J; Mackway-Jones, K
Abstract : Background: The thrombolysis in myocardial infarction (TIMI) risk score has been shown to risk stratify patients with suspected acute coronary syndromes (ACS) effectively in the emergency department (ED) but cannot be used to guide patient disposition. We aimed to evaluate whether modifying the TIMI risk score to give greater weighting to ischaemic ECG changes and troponin elevations would enhance its risk stratification and thus potentially facilitate safe patient discharge after 12-h troponin testing. Methods: A prospective diagnostic cohort study was performed within the ED at Manchester Royal Infirmary, a university-affiliated teaching hospital with an annual ED census of approximately 145 000 patients. 804 patients who had presented to the ED with suspected cardiac chest pain were recruited. All patients underwent 12-h troponin T testing and were followed up by telephone and chart review after 30 days for the composite primary outcome of death, acute myocardial infarction (AMI) or urgent coronary revascularisation. Results: The modified TIMI risk score outperformed the original (area under the receiver operator characteristic curve 0.87 versus 0.77, p<0.001). Using a cut-off of more than 2 points the score had a sensitivity of 96.4% for the prediction of 30-day events. The specificity of the score was only 51.0%, suggesting that in practice over 40% of patients would be ineligible for discharge even after troponin testing. Conclusions: Modifications to the TIMI risk score can improve its performance in the risk stratification of patients presenting to the ED with chest pain. However, a lack of specificity may still limit its use for guiding patient disposition after troponin testing.